Revisiting Sustainability in Tropical Heritage Building: Architectural Lessons from Gereja Blenduk - Maria Rosita Maharani (TERRACE: JOURNAL OF ARCHITECTURE & URBAN STUDIES, 2026)
The increasing level of environmental degradation has led to a decline in environmental quality, both at present and in the future. Since buildings contribute more than 30% of global emissions, building design should incorporate and implement sustainability principles. Understanding sustainability can be achieved not only through newly constructed buildings but also through the study of historic buildings. The preservation and adaptive reuse of older buildings represent an important sustainability strategy, as they maintain historical value while reducing the demand for new material resources. This study aims to analyze sustainable architectural principles in historic buildings, Gereja Blenduk as the case study. Employing a descriptive analytical research method, the findings indicate that the church reflects the application of comprehensive sustainability principles, including urban ecology, energy strategies, water management, material use, waste management, community engagement, cultural preservation, local economic strategies, and operational management. Many of these sustainability practices have developed contextually through adaptation to climate conditions, cultural values, and the social functions of the surrounding area. Therefore, Gereja Blenduk can be regarded as a tangible example of how historic buildings can adapt to sustainability principles while maintaining their authenticity.